FREQUENCY OF COMMON BACTERIA AND THEIR ANTIBIOTIC SENSITIVITY PATTERN IN DIABETICS PRESENTING WITH FOOT ULCER - Rahim, Fawad; Ullah, Fahim; Ishfaq, Muhammad; Afridi, Ayesha Khan; Rahman, Sadiq ur; Rahman, Hassan (Journal of Ayub Medical College Abbottabad, 2016)
Background: Foot ulcers are one of the most important complications of diabetes mellitus and often lead to lower limb amputation. Diabetic foot ulcers are susceptible to infection. The objective of this study was to determine the frequency of common bacteria infecting these ulcers and their antibiotic sensitivity pattern. Methods: This descriptive cross-sectional study was performed in the Departments of Medicine and Surgery, Khyber Teaching Hospital, Peshawar from April, 2011 to February, 2012. Specimens collected from ulcers of 131 patients were inoculated on Blood Agar and MacConkey Agar, and antibiotic sensitivity was tested using standard disc diffusion method. Results: Out of 131, specimens from 120 patients yielded 176 bacteria. Sixty-six patients had monomicrobial infection while polymicrobial growth was obtained in 54 patients. Overall, Staphylococcus aureus (38.6%) was the most common isolate followed by Pseudomonas aeruginosa (27.3%). Staphylococcus aureus was most often sensitive to Moxifloxacin, Imipenem/Meropenem, Vancomycin and Linezolid while it showed varying sensitivity to Penicillins and Cephalosporins. 47.1% isolates of Staphylococcus aureus were resistant to Methicillin. Most of the gram negative rods were sensitive to Imipenem/Meropenem, Piperacillin-Tazobactam and Ticarcillin-Clavulanate. Majority of gram negative bacteria were found resistant to Cephalosporins and Moxifloxacin except Pseudomonas which showed variable sensitivity to Ceftriaxone, Ceftazidime and Moxifloxacin. Conclusions: Majority of isolates were found resistant to the commonly used antibiotics. Most commonly isolated bacterium, Staphylococcus aureus was most often sensitive to Moxifloxacin, Imipenem/Meropenem, Vancomycin and Linezolid, while majority isolated gram negative rods were sensitive to Imipenem/Meropenem, Piperacillin-Tazobactam and Ticarcillin-Clavulanate. Keywords: Diabetes mellitus, foot ulcers, infection, antibiotic sensitivity